Plain, honest men : the making of the American Constitution - Beeman, Richard R. (New York : Random House, 2009)
From distinguished historian Richard Beeman comes a dramatic and engrossing account of the men who met in Philadelphia during the summer of 1787 to design a radically new form of government. Beeman takes readers behind the scenes and beyond the debate to show how the world's most enduring constitution was forged through conflict, compromise, and, eventually, fragile consensus during a time when many Americans feared that a combination of financial distress and civil unrest would doom the young nation's experiment in liberty.
Principal characters -- The Constitutional Convention of 1787: a chronology -- The crisis -- The indispensable men of the Convention -- The delay that produced a revolution -- The Convention opens for business -- A high-stakes gamble -- "We the people" or "We the states"? Creating the American Congress -- Imagining the American presidency -- Counterattack -- "We are now at full stop" -- The Fourth of July, 1787 -- Compromise: large states, small states, slave states, and free states -- Beyond the Connecticut Compromise -- "The people are the King" -- Fashioning a first draft of the Constitution: July 27 - August 6 -- Revising the Constitution: August 6-31 -- The "general welfare" and the presidency -- "The paradox at the nation's core" -- A fragile consensus: Sep 10-15 -- Sep 17: Day of decision -- The People's Constitution: "Federalists" seize the initiative -- Achieving a more perfect union: the Federalists prevail -- "A Republic, if you can keep it" -- Full list of delegates to the Constitutional Convention of 1787 -- U. S. Constitution (Sep 17, 1787), Article I-VII -- A note about quotations.
Includes bibliographical references (p. [447]-448) and index.
Keywords: United States. -- Constitutional Convention -- (1787); Constitutional history -- United States